واقع اقتصاد المعرفة في الجامعات اليمنية من وجهة نظر اعضاء هيىة التدريس: دراسة ميدانية في جامعتي صنعاء والعلوم والتكنولوجيا اليمنية - Al-Azizi, Mahmood Abdo Hasan; Al-Hidabi, Dawood Abdulmalek Yahya (2018)

(untitled)
The purpose of the research was to assess the current situation of the knowledge economy in the Yemeni universities (Public and private) from the point of view of their faculty members. A further investigation into the possible significant differences between faculty members’ views regarding the knowledge economy in both Yemeni public and private universities was also attempted. In order to achieve the objectives of the research, the researchers used the descriptive approach, and designed a questionnaire as the research tool which consisted of four main dimensions: research, development, innovation, education and training, ICT infrastructure, and governance. The validity and reliability of the tool were statistically checked, and data was analyzed using SPSS program. The study revealed the following results: - The current knowledge economy at Sana’a University was rated as very low by the faculty members. - The current knowledge economy at the University of Science and Technology was rated by the academic staff as medium. - There were statistically significant differences between the opinions of the members of the research sample in favor of the University of Science and Technology. A number of recommendations and suggested areas for further research were proposed.